Without the filmmaking there is no research: establishing the Sound/Image Cinema Lab via a REF2021 impact case study and exploring the impact of its engagement with UK film production. Issue 2 (3rd April 2022) - Fox, Neil
ABSTRACT: This article discusses the writing of an impact case study for REF2021 that revolves around independent film production, film industry and pedagogy. The culture of professional film production at Falmouth University's School of Film & Television resulted in involvement in the BAFTA winning Mark Jenkin film Bait (2019) and the widespread impact of that film provided the impetus for an impact case study that saw the consolidation in the form of the Sound/Image Cinema Lab (The Lab) project. Bait is one of several commercial short and feature film productions that have received interventions that have resulted in the production and/or completion of work that would not have been possible, or not possible to the same level of quality, without it. This article tracks how those interventions impacted beneficiaries and stakeholders culturally, socially and economically and resulted in national and regional economic and production benefits for film production and graduate career development. It discusses how these interventions and productions were configured as research to ensure that the impact of Bait and other films were measured and captured. It extends work delivered by the author in Media Practice & Education [Fox, Neil. 2018. "'Filmmaking is a Hard Thing to Do': Reflections on Student and Lecturer Experience of Falmouth University's Filmmaker in Residence Initiative." Media Practice and Education 19 (2): 205–221].